Surgical correction of pes planovalgus deformity in ankle osteoarthritis: clinical and functional outcomes - A. A. Shirinov; N. V. Zagorodniy; D. V. Burkov; M. A. Imankulov; A. R. Zakirova; A. A. Neverova (Genij Ortopedii, 2026)
Introduction Pes planovalgus is a progressive, collapsing deformity of the foot, stage IV (subtype IV B according to the Myerson classification), associated with ankle joint involvement. This pathology remains one of the most complex and disabling in foot and ankle surgery. Surgical correction of the hindfoot associated with ankle osteoarthritis suggests careful planning and may include isolated arthrodesis procedures and strategies to be followed by total ankle arthroplasty. The objective was to evaluate the clinical and functional results of surgical correction of pes planovalgus deformity in patients with concomitant ankle osteoarthritis. Material and methods This retrospective, single-center study included data from 13 surgically treated patients with stage IVB flatfoot deformity and concomitant ankle osteoarthritis. All patients underwent surgery to correct the hindfoot deformity, using various arthrodesis procedures depending on the clinical situation. Clinical and functional outcomes were assessed using the Visual Analogue Scale (VAS), the AOFAS scale, and the FAOS questionnaire before and after surgery. The minimum follow-up period was 12 months. Statistical analysis was performed using the Wilcoxon signed-rank test with exact two-tailed p values calculated. Results Postoperatively the median VAS score decreased from 8 [7; 8] to 2 [2; 3.5] scores (p = 0.000244). The median FAOS score increased from 22 [16.5; 42] to 86 [69; 89.5] (p = 0.001709). The median AOFAS score improved from 40 [32.5; 42.5] to 88 [80; 90] (p = 0.000977). Discussion The findings are consistent with those reported in international literature and demonstrate the high efficacy of hindfoot arthrodesis in this condition. Significant improvement in the functional parameters suggests the appropriateness of the surgical approach. In some cases, hindfoot arthrodesis can be considered as the first step prior to the total ankle arthroplasty. Conclusion Surgical correction of pes planovalgus deformity through hindfoot arthrodesis provides a statistically significant reduction in pain and improved functional status in patients with concomitant ankle osteoarthritis.